Reversing the reversed congruency effect: directional salience overrides social significance in a spatial Stroop task - Yoshihiko Tanaka; Matia Okubo (i-Perception, 2024)
In a spatial Stroop task, eye-gaze targets produce a reversed congruency effect (RCE) with faster responses when gaze direction and location are incongruent than congruent. On the other hand, non-social directional targets (e.g., arrows) elicit a spatial Stroop effect (SSE). The present study examined whether other social stimuli, such as head orientation, trigger the RCE. Participants judged the target direction of the head or the gaze while ignoring its location. While the gaze target replicated the RCE, the head target produced the SSE. Moreover, the head target facilitated the overall responses relative to the gaze target. These results suggest that the head, a salient directional feature, overrides the social significance. The RCE may be specific to gaze stimuli, not to social stimuli in general. The head and gaze information differentially affect our attentional mechanisms and enable us to bring about smooth social interactions.